2012
DOI: 10.1002/hep.25947
|View full text |Cite
|
Sign up to set email alerts
|

Second infections independently increase mortality in hospitalized patients With cirrhosis: the north american consortium for the study of end-stage liver disease (NACSELD) experience

Abstract: Bacterial infections are an important cause of mortality in cirrhosis but there is a paucity of multi-center studies. The aim was to define factors predisposing to infection-related mortality in hospitalized cirrhotic patients. Methods A prospective, cohort study of cirrhotic patients with infections was performed at eight North American tertiary-care hepatology centers. Data were collected on admission vitals, disease severity [MELD and sequential organ failure (SOFA)] scores], first infection site, type [co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
371
4
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 365 publications
(391 citation statements)
references
References 24 publications
15
371
4
1
Order By: Relevance
“…In contrast to antimicrobials that disrupt the normal gut microbiome, facilitating the proliferation of C. difficile, 34 and in contrast to gastricacid suppressive medication that may allow survival of vegetative forms of C. difficile, 35 a plausible biological mechanism for the observed association could be the negative impact of corticosteroids on the gastrointestinal mucosal integrity. 36 Previous studies found that gastrointestinal comorbidities such as inflammatory bowel disease 12 and cirrhosis 14 were associated with a worse prognosis in patients with CDI. Similarly, congestive heart disease, chronic pulmonary disease, renal failure, and malignant neoplasms were also associated with higher mortality rates among inpatients with CDI.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to antimicrobials that disrupt the normal gut microbiome, facilitating the proliferation of C. difficile, 34 and in contrast to gastricacid suppressive medication that may allow survival of vegetative forms of C. difficile, 35 a plausible biological mechanism for the observed association could be the negative impact of corticosteroids on the gastrointestinal mucosal integrity. 36 Previous studies found that gastrointestinal comorbidities such as inflammatory bowel disease 12 and cirrhosis 14 were associated with a worse prognosis in patients with CDI. Similarly, congestive heart disease, chronic pulmonary disease, renal failure, and malignant neoplasms were also associated with higher mortality rates among inpatients with CDI.…”
Section: Discussionmentioning
confidence: 99%
“…The APASL group considers only hepatic insults/injury as acute precipitating event, whereas EASL also includes extrahepatic insult such as the sepsis and upper gastrointestinal bleeding as a cause of acute insult. 2,[4][5][6][7] The chronic liver failure (CLIF) acute-on-chronic liver failure in cirrhosis (CANONIC) study has defined ACLF based on increased 28-day mortality in patients with liver cirrhosis and acute decompensation. In a previous study, we have demonstrated chronic liver failure-sequential organ failure assessment (CLIF-SOFA) criteria to be better than APASL criteria in defining ACLF.…”
mentioning
confidence: 99%
“…(1,31) Patient data were recorded in a REDCAP database. The study protocol was approved by the institutional review boards in all participating centers, and all patients or their family members provided written informed consent for study inclusion.…”
Section: Methodsmentioning
confidence: 99%